Al-Musytarak Al-Lafdzi Fii Al-Qur’an Al-Karim (Lafdzah Al-Hikmah Namudzajan) - Agus Yasin; Ahmad (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2021)
Polysemy refers to the phenomenon in which a single lexical item possesses multiple related meanings depending on its linguistic and contextual use. The term al-ḥikmah (wisdom) in the Qur'an represents one such example, as its meaning varies across different verses and contexts. These semantic variations indicate that al-ḥikmah functions as a polysemous lexical item rather than conveying a single fixed meaning. This study aims to examine the polysemous meanings of al-ḥikmah in the Qur'an through an analysis of classical Arabic dictionaries and Qur'anic exegeses (tafsīr). This research employed a qualitative descriptive approach based on library research. Data were collected from Qur'anic verses containing the term al-ḥikmah and analyzed by comparing lexical definitions with interpretations provided by classical and contemporary exegetes. The findings reveal that the root word ḥakama, from which al-ḥikmah is derived, is associated with the basic meaning of restraining, judging, or preventing error. The study identifies that derivatives of this root occur in approximately 210 Qur'anic verses, while the noun al-ḥikmah itself appears 20 times across 20 verses in 12 chapters (sūrahs). Contextual analysis demonstrates that al-ḥikmah carries several related meanings, including al-mawʿiẓah (admonition), al-sunnah (the Prophetic tradition), al-nubuwwah (prophethood), al-fahm (understanding), al-Qur'an, and ʿulūm al-Qur'an aw tafsīruhu (the sciences or interpretation of the Qur'an). Although scholars generally agree on five of these semantic interpretations, they differ regarding whether al-sunnah should be regarded as one of the meanings of al-ḥikmah. These findings demonstrate the richness of Qur'anic semantics and highlight the importance of contextual interpretation in understanding polysemous lexical items.